Decision Tree of Materials: A Model of Halal Control Point (HCP) Identification in Small-Scale Bakery to Support Halal Certification - Sucipto Sucipto; Reza Wahyu Damayanti; Claudia Gadizza Perdani; Muhammad Arif Kamal; Retno Astuti; Nur Hasanah (International Journal of Food Science)
A bakery is a business that bakes flour-based foods, including bread, cookies, cakes, pastries, and pies, and sells them. Some bakeries are also categorized as large scale, medium scale, and small scale. Halal embraces all food category; bakery product can satisfy the challenge and opportunity of halal food segment market. The small-scale bakery will benefit from creating a halal certification to attract new customers. The first stage of submission for halal certification is identifying Halal Control Points (HCP) of materials and production. The material tracing uses a decision tree. The purpose of this study is to identify HCP in materials and production processes and provide alternative improvements. Identification of HCP in material decision trees to determine contains non-HCP (halal) material, HCP material, and haram (forbidden) material. Happy Cake bakery uses 75% non-HCP (halal) materials and 25% HCP (noncertified halal) materials from 80 ingredients. Bakery Canggi Fully has 83.3% halal materials and 16.6% noncertified halal materials from 24 ingredients. Bakery MacCheese has 79% of halal materials and 21% of noncertified halal materials from 43 ingredients. The decision tree makes it very easy to identify the halal status of ingredients. The HCP ingredients need to be replaced with clearly halal ingredients. Substitution of HCP material to halal-certified ingredients may affect production costs, product quality, and profit. Therefore, it is necessary to choose a suitable halal material. Halal certification requires a high commitment of small-scale bakery businesses.